Sinus Grafting Techniques A Step-by-Step Guide - Younes, Ronald; Nader, Nabih; Khoury, Georges (Springer International Publishing : Imprint: Springer, 2015)
Placement of endosseous implants in the posterior maxilla is often difficult because of a lack of supporting bone. Sinus augmentation procedures have therefore been extensively used for the treatment of the edentulous atrophic posterior maxilla prior to implant placement. This book describes in detail the most widely used sinus grafting techniques as well as some innovative variations, with full coverage of both lateral and crestal approaches. A key aim is to assist the practitioner in selecting the appropriate sinus grafting technique based on the evaluation of a number of parameters that are described in detail and codified in a simple and practical way. Up-to-date information is also provided on grafting materials and on potential complications of sinus augmentation procedures and their treatment.